Aktivitas Hepatoprotektor Fraksi Polar n-Butanol Rambut Jagung (Zea mays L.) Terhadap Tikus Putih Jantan yang Diinduksi Paracetamol - Nessa, Nessa; Putri , Noni Rahayu; Mutmaina , Iim (Journal of Pharmaceutical and Sciences, 2026)
Corn silk is a part of the corn plant that is known to contain beneficial chemical compounds, including flavonoid compounds that have antioxidant activity and have the potential as hepatoprotective compounds that can protect the liver from damage caused by free radicals. The purpose of this study was to determine the hepatoprotective effect of the polar fraction of corn silk on male white rats induced by paracetamol. The animals used were 25 male white rats divided into 5 groups, namely group 1 (Negative control), group 2 (positive control) induced by toxic doses of paracetamol, and groups 3, 4, 5 polar fractions of corn silk doses (200, 400, 800 mg/kgBW). The measurement parameters were SGOT-SGPT levels, liver organ weight ratio, and histopathological examination of the liver. The data obtained were analyzed descriptively and statistically with two-way ANOVA followed by Duncan's test. The results of observations of SGOT enzyme levels on days 7 and 14 were group 1 (18.5 and 20.5 U/L), group 2 (50.5 and 113.75 U/L), group 3 (21.5 and 45.25 U/L), group 4 (23.25 and 83.75 U/L), group 5 (26.5 and 105.75 U/L). SGPT enzyme levels on days 7 and 14 were group 1 (39.75 and 42 U/L), group 2 (70.25 and 82.25 U/L), group 3 (42.5 and 48 U/L), group 4 (46.26 and 64.75 U/L), group 5 (48.75 and 70.25 U/L). The results of histopathological observations with score values of group 1 (0), group 2 (4), group 3 (1), group 4 (3), group 5 (3). Based on the research results obtained, it can be concluded that the polar fraction of corn silk has the most effective hepatoprotective activity at the lowest dose of 200 mg/kgBW with the observation results closest to the negative control for each parameter.